46 Using a quality improvement approach to improve treatment escalation plans and reduce cardiac arrests at a large acute nhs trust. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hurlow, Adam; Pattison, Craig; Cracknell, Alison; Winfield, Anna; Nair, Sherena
Abstract : Background: Cardiopulmonary resuscitation (CPR) is effective for a minority of patients, with survival to discharge of less than 20%. A recent UK review of in-hospital CPR attempts identified failure to recognise patients at risk of cardiac arrest, discuss treatment escalation plans (TEPs) including CPR, and make do not attempt CPR decisions. Methods: In 2014, Leeds Teaching Hospitals NHS Trust (LTHT) established a quality improvement (QI) collaborative to improve the care of patients at risk of clinical deterioration and reduce avoidable deterioration or inappropriate CPR. It consisted of 14 pilot wards across specialty areas, supported by a multi-disciplinary faculty including Palliative Care. Three key drivers for change were identified, including a work-stream focussed on timely TEPs for patients nearing the end of life. Over 12 months, pilot wards developed and tested improvement ideas. In June 2015, a bundle of five key interventions, including a TEP sticker and decision prompts, safety huddles and post-CPR debrief, was tested successfully across the 14 wards. A staggered trust-wide roll out of the bundle started in March 2016. Results: Statistical process control charts have shown a sustained and significant 25% reduction in cardiac arrest calls across LTHT, and a 32% reduction at the Saint James's University Hospital Site. This equates to 87 fewer cardiac arrests annually across the Trust than in 2015. On pilot wards the proportion of patients with a treatment escalation plan and a CPR decision increased by 125% and 72%, respectively. The Trust incidence of cardiac arrests per 1000 admissions at SJUH is now 25% lower than the national average. Conclusion: A QI collaborative approach, empowering ward level innovation, with expert faculty support, can improve recognition of patients at risk of cardiac arrest, change behaviours and increase the number of patients with TEPs including CPR decisions; leading to a statistically significant reduction in cardiac arrests.